ANALISA PENGARUH DESAIN PRODUK, PERSEPSI HARGA, DAN KUALITAS PRODUK TERHADAP CITRA MEREK UNTUK MENINGKATKAN MINAT BELI KONSUMEN SEPATU ADIDAS ORIGINAL (Studi Kasus pada Masyarakat di Kota Semarang) - Anandia, Rizky; Santosa, Suryono Budi (Diponegoro Journal of Management, 2015)
The problem in this research is top brand index of adidas shoes  decline in 2012-2014. This reaserch aims to test the strength of the product design, quality of the product and price perception against a brand image to improve purchase intentiont on a adidas shoes (a case study in Semarang). This reaserch uses three independent variabels namely product design, price perception and quality of the product. Purchase intention as the dependent variable and then the variable brand image as intervening variable.A method of this research technique using non-probability sample that is purposive sampling to sample as many as 150 of respondents semarang city people who have knowed  adidas shoes .A method of data analyst using a technique double regression analysis , the analysis includes: test the validity of , a test of reliability , test the assumption of the classics , linear regression test doublet test , test f , test the coefficients determined and test sobel.The results show significant  and positive effect product design to brand image, significant and positive effect price perception to customer value, significant and positive effect quality of the product to brand image, and then significant and positive brand image  to purchase intention.